Facilitative interpersonal skills are relevant in child therapy too, so why don’t we measure them? - Jordan Bate (Research in Psychotherapy, 2022)
One of the consistent findings from psychotherapy process research has been the impact of therapist effects on patient change and the therapeutic alliance. The Facilitative Interpersonal Skills (FIS) paradigm is a task in which participants respond to standardized videos of actors playing patients in interpersonally challenging moments as if they were the therapist, which was designed to assess therapist effects. Participants’ video recorded responses are coded for eight skills: verbal fluency, emotional expressiveness, warmth/acceptance/ understanding, empathy, persuasiveness, hope/positive expectations, alliance-bond capacity, and rupture-repair responsiveness. Performance-based procedures like the FIS minimize self-report bias and systematically control for client-related variability while maintaining strong clinical relevance. Research has shown that therapist FIS predicts the quality of the therapeutic alliance and outcome in adult psychotherapy. This paper describes the development and first adaptation of the FIS task using child and adolescent patients as the stimuli, and reports findings from a pilot study testing the reliability. The FIS-Child (FIS-C) task was administered to 10 therapists with a range of clinical backgrounds. Participants also completed the original FIS task and self-report measures of their empathy, social skills, and playfulness. Adequate interrater reliability was achieved on the FIS-C. There were no significant differences between participants’ ratings on the FIS-C compared to the original FIS, although there were minor differences in the correlations between the FISC and self-report measures compared to the original FIS. Findings support moving forward with utilizing the FIS-C to empirically study therapist effects that may be common factors across treatment models.